The Censorship of Sex: A Study of Raymond Chandl er’s The Big Sleep in Franco’s Spain - Linder, Daniel (TTR : traduction, terminologie, rédaction, 2004)
AbstractDuring the period when General Francisco Franco ruled Spain (1936-1975), official censorship kept a watch on all books that were published in the country. The main objective of this censorship was to conceal from the Spanish people political manifestations that might be ultimately threatening for the dictatorial government politically. However, under heavy influence of the Catholic Church, the censors also veiled for the moral health of the Spanish people by intervening in all matters of sexual morality, decency, obscenity and vulgarity. Research has shown that during this period censors were as vigilant for sexual content as they were vigilant for political content. In this study I will examine censorship and sex by studying Raymond Chandler’s first novel, The Big Sleep (1939) and the three Spanish-language translations published during this period (1949, 1958, 1972). Chandler’s novel contains no potential political offenses to Franco’s Regime and its allies, but it does contain references to male homosexuals, scenes of female nudity, and sexually suggestive dialogues involving the detective and a female character. All of the Spanish versions were censored, whether by government censors or the translators/editors prior to presenting the manuscript to the censors. I will discuss the government-censored and self-censored passages in the Spanish versions of the novel, and show that all of the references to the homosexual characters, much of the nudity, and many of the sexually-suggestive dialogues have been manipulated and/or suppressed, producing undesirable and often unexpected effects.